INVESTIGATION OF SERUM CALCIUM, VITAMIN D WITH THYROID HORMONES AND BMD IN HYPOTHYROID AND EUTHYROID PATIENTS - Sheikh, Zeenath S; Sharma , Manmohini (ShodhKosh: Journal of Visual and Performing Arts, 2022)
The emergence of bones-related pathologies and anomalies due to nutritional, bone, and metabolic mineral inadequacies is a major concern for the nation’s health. The objective of this research is to compare the bone mineral density (BMD), blood the mineral calcium, and blood vitamin D levels in underweight and a healthy thyroid individual in relation to their thyroid hormones. The concentration of calcium in the blood was measured using the Arsenazo III Procedure. We looked at how the thyroid hormones affected a number of different factors. Statistical significance was defined as a p-value less than 0.05. The entire calculation was executed through the software for statistical calculations SPSS 21, a product of IBM USA. In individuals with normal thyroid function, there had been a beneficial relationship between vitamin D consumption and both “T3 (r2= 0.04, p<0.01)” as well as “FT4 (r2= 0.1, p<0.01).” Vitamin D and bone mineral density (BMD) at the collarbone region were shown to be significantly correlated “(r2= 0.008, p<0.05)” in the present study. Vitamin D level and urinary calcium levels were found to be positively correlated, according to the data. “(r2= 0.56, p<0.01)”.